Space–time fixity and flexibility of daily activities and the built environment: A case study of different types of communities in Beijing suburbs. (July 2015) - Shen, Yue; Chai, Yanwei; Kwan, Mei-Po
Highlights: Examine space–time fixity/flexibility of activities from a time-geographic perspective. Investigate how space–time fixity/flexibility vary among different types of communities. Danwei, commodity housing, affordable housing and relocated housing are considered. The relationships between STF and the built environments of different community types are different. Gender and age differences are not consistent with what was observed in Western countries. Abstract: Space–time fixity constraint is an important concept in transport geography, but the influence of the built environment around both people's residence and activity locations is not clear. Due to the housing reform and rapid suburbanization in China, various types of residential communities and diverse built environments coexist in the suburbs. Comparing how people's space–time fixity/flexibility varies among different community types and built environments can thus enhance our understanding of the transition process in Chinese cities. This study investigates how space–time fixity/flexibility and their relationships with the built environment vary among different types of residential communities in Beijing suburbs. Activity-travel diary and 7-day GPS tracking data of 709 respondents in Shangdi-Qinghe area of Beijing collected in 2012 were used. We investigate how variations in space–time flexibility are associated with built environment factors and four different community types: danwei communities, commodity housing communities, affordable housing communities and relocated housing communities, controlling for personal, household and activity attributes. The results suggest the influences of the built environments at residential place and activity place are different, and the relationships between space–time fixity and the built environments of different community types are different. Space–time fixity is not so sensitive to the built environment for residents in danwei communities and affordable housing communities. Gender and age differences in space–time fixity are not consistent with what was observed in Western countries. This seems to reflect the influence of unique social, cultural and family norms in China.